Some determinants of Stunting in children of Tehran - Esfarjani, Fatemeh; Roustaee, Roshanak; Mohammadi, Fatemeh (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Stunting indicates longWterm effects of inadequate nutrition and/or health. This study aimed to investigate the factors influencing stunting among first grade primary school children in Tehran, Iran 2008. Material and Method: This is a case-control study. The subjects were selected from 3147 Children whose height was measured using standard protocols. 86 stunned children (Case group) and 308 children with normal height recruited for the study, using a cluster sampling method in 5 districts of Tehran. Stunting was defined as the height for age below the 5th percentile of CDC2000 standard. The tool for data collection was a questionnaire including questions about children's birth weight and height, duration of breast feeding and demographic characteristics. Data were analyzed by SPSS14 and using Chi-square, student t-test and multivariate logistic regression. Results : The prevalence of stunting was %3.7 among children. Means for birth weight and duration of breast feeding were 2.9±0.6 kg, 17.4± 8.7 months, respectively among stunted children which were significantly lower than non stunted children (3.2 ± 0.5 kg 20± 7.7 months, respectively) (P<0.05).The parents of stunted children had lower education (P<0.05). Logistic regression analysis showed that odds ratio of stunting among children is 4.6 for children with "birth weight of lower than 3Kg" compared to children with "birth weight higher than 3Kg" (CI= 95%; OR:1.4-14.7). Odds ratio of stunning was also 3.3 (CI= 95%; OR: 1.1-9.2) among children with "breast feeding less than 3months" compared to "breast feeding more than 3 months" . It was also 6.7 (CI= 95%; OR: 1. 1-9.2). Conclusion: This study showed that the prevalence of stunting is relatively low in Tehran. Primary health care during pregnancy and breast feeding in first 3 month of life were shown as the most important factors influencing stunting. Key Words : Children, Stunting, Birth weight, Breast feeding, Parents education Corresponding Author: Fatemeh Esfarjani. Department of Food and Nutrition Policy and Planning Research, National Nutrition and Food Technology Research Institute, Faculty of Nutrition Sciences and Food Technology, Shahid Beheshti University of Medical Sciences, Tehran, Iran. REFERENCES -ACC/SCN (2000). Fourth Report on the World Nutrition Situation.Geneva: ACC/SCN in collaboration with IFPRI. -Amigo H et al (2001). Growth deficits in school children. Journal of Nutrition. 13 (2) 251-254. -Biswas S Bose K (2010). Sex differences in the effect of birth order and parents educational status on stunting: A study on Bengalee preschool children from eastern India, HOMO. Journal of Comparative Human Biology. 61 (4) 271-276. -Blake J (1981). Family size and the quality of children. Demography. 18 (4) 421-42. -Bronte-Tin Kew J DeJong G (2004). Children's Nutrition in Jamaica: Do household structure and household economic resources matter? Social Science& Medicine.58 (3) 499-514. -De Onis M and Blössner M (2003). The World Health Organization Database on Child Growth and methodology and applications. International Journal of Epidemiological association 32 (4) 518-26. -Fesharakinia A Sharifzadeh Gh R Zarban A (2008). [Investigation of nutritional status in elementary school students of South Khorasan province: East of Iran]. Qom University of Medical Sciences Journal. 2(3) 47-72. (Persian). -Frangillo EA de Onis M Hanson KMP (1997). Socioeconomic and demographic factors are associated with Worldwide Patterns of Stunting and Wasting of Children. Journal of Nutrition, 127 (2) 2302-9. -Ghorbani J (1998). [A study of malnutrition at the primary school students in Zanjan]. Journal of Zanjan University of medical Science & Health Service, 23 (6) 24-31. (Persian). -Gibson R Ferguson EL (1998). Nutrition intervention strategies to combat zinc deficiency in developing countries. Nutrition Research Reviews. 11. 115-31. -Heer DM (1986). Effect of number, order, and spacing of siblings on child and Adult Outcomes: An overview of Current Research. Biodemography and Social Biology. 33 (1-2) 201-4. -Ibrahim SA Maksoud AAE Nassar MF (2002). Nutrition stunting in Egypt: which nutrient is responsible? Eastern Mediterranean Health Journal, 8(2-3) 272-8. -Kariuki F Monari J Kibui M et al (2002). Prevalence and risk factors of malnutrition. Journal of National Institute of Public Health. 51(1) 44-50. -Kikafunda J et al (1998).Risk Factors for Early Childhood Malnutrition in Uganda. J Pediatrics. 102 (4) E45. -Killic I et al (1998). The effect of zinc-supplemented bread consumption on school children with asymptomatic zinc deficiency. Journal of Pediatric Gastroenterology and Nutrition. 26 (2) 167-71. -Lwambo N et al (2000). Age patterns in stunting and anaemia in African school children: A cross-sectional study in Tanzania. European Journal of Clinical Nutrition. 54(1) 36-40. -Marquis GS et al (1997). Association of Breastfeeding and Stunting in Peruvian Toddlers: An Example of Reverse Causality. International Journal of Epidemiology. 26 (2) 349-356. -Marshall WA Tanner JM (1970). Variations in the pattern of pubertal changes in boys. Archive of Diseases in Childhood. 45 (239) 13-23. -Ninh N et al (1996). Zinc supplementation increases growth and circulating insulin- like growth factor 1 (IGF-1) in growth- related Vietnamese children. The American Journal of Clinical Nutrition. 63 (4) 514-9. -Prasad AS (1996). Zinc deficiency in women, infants and children. Journal of American College of Nutrition, 15 (2) 113-120. -Ricci J Becker S (1996). Risk factors for wasting and stunting among children in Metro Cebu, Philippines. The American Journal of Clinical Nutrition. 63 (6) 966-75. -Rosado JL et al (1997). Zinc supplementation reduced morbidity, but neither zinc nor iron supplementation affected growth or body composition of Mexican preschoolers. The American Journal of Clinical Nutrition. 65 (1) 160-1 -Semba R et al (2008). Effect of parental formal education on risk of child stunting in Indonesia and Bangladesh: A cross-sectional study, lancet. 371 (9609) 322-328 -Shah SM et al (2003). Prevalence and correlates of stunting among children in rural Pakistan. Pediatrics International, 45(1) 49-53. -Shekholeslam R et al (2000). Current status and trends in the 10-years indices of malnutrition in children under 5 years. Iranian journal of Epidemiology. 4 (1) 21-28. -Sichieri R et al (1993). Nutrional status of children and occupational categories of the family in rural community of Parana Brazil. Cad saude publica. 9 (1) 28-35. -Taguri A et al (2008). Risk factors for stunting among under-fives in Libya. Public Health Nutrition, 12 (8) 1141-9. -Taheri f A Fesharakinia Saadat Joe A (2001). The prevalence of underweight, wasting and stunting in 6-12 years old children of Birjand. Journal of Birjand University of Medical Sciences. 8 (1) 22-27. -Trahms C Mckean K (2008). Nutrition during Infancy in: Mahan LK, Escott-Stump S. Krause's food, nutrition and diet therapy, Missouri, Saunders co. -Unicef Statistics (2008). World Wide Prevalence of malnutrition among children under 5 years. available at:[http://www.childrenfo.org/areas/malnutrition](Accessed January) -Yang XL et al (2010). Analysis of influencing factors for stunting and underweight among children aged 3-6 years in 15 counties of Jiangsu and Zhejiang provinces. Zhonghuz Liu Xing Bing Xue Za Zhi. 31 (5) 506-509.